Cancer-related anemia – diagnosis and treatment - Pawlak, Wojciech; Wawrocka-Pawlak, Marlena (Contemporary Oncology/Współczesna Onkologia, 2006)
Cancer-related anemia is an important clinical factor in the treatment of malignant diseases. A correct approach to therapy should consider all the possible causes and patients need to be treated accordingly. Anemia negatively affects patients” quality of life, and is an adverse prognostic and predictive factor. Until the 1990s, transfusions as well as iron and vitamins repletion were the only treatment options for anemia. Over the last decade, clinical trials with epoetins have been conducted in a variety of settings in oncology. There are consistent evidences that administration of epoetins reduces the relative risk for blood transfusions and the number of blood units transfused in cancer patients. Moreover, epoetins significantly improve quality of life.